Investigating the influencing factors of municipal solid waste generation in the Kuala Terengganu by correlational analysis / Mohd Nur Hakimi Ramzi Abd Samad and Siti Norashikin Mohamad Shaifuddin - Abd Samad, Mohd Nur Hakimi Ramzi; Mohamad Shaifuddin, Siti Norashikin (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Municipal solid waste (MSW) management is a challenge for local authorities to ensure adequate resources is provided, but it requires a high cost in budget expenditure with the use of approximately 20% to 50% of their available municipal budget to fulfil the task. The identification of the contributing factors in generation of MSW are important to provide a picture in future planning for sustainable waste management to the authority. Therefore, this study aims to identify factors associated with MSW generation in Kuala Terengganu. In this study, data of MSW generation from 2017 to 2019 is obtained from Kuala Terengganu City Council based upon total weight of MSW collected from each administrative division and the contributory factors (population, number of residential premises and number of commercial premises) were analyzed to determine any significant relationship associates with MSW generation using IBM SPSS version 26. The result shows the mean of MSW generation and waste per capita from 2017-2019 in the District of Kuala Terengganu is 2818.53 metric tons and 0.65 kg/capita/day, respectively, and the growth rate of MSW generation was in constant of 5% in 3 years. Statistical analysis shows there is a significant strong correlation between the population and the number of commercial premises with MSW generation in Kuala Terengganu (p<0.01). The findings of this study can provide a baseline for the city council in arranging the resources in their further planning budget for the future to cater the need required in managing the MSW generation at each administrative division over time.